2016
DOI: 10.5812/hepatmon.37447
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Against Hepatitis A for Hemophilic Patients: Is It Necessary?

Abstract: BackgroundHemophilic patients require long-life intravenous infusion of factor concentrates to treat bleedings. This could increase the risk of transmission of blood-borne infections like hepatitis C.ObjectivesThe current study was aimed at investigating the immunity status against hepatitis A in hemophilic patients in south Khorasan and evaluating the necessity of hepatitis A vaccination for this population.Patients and MethodsA cross-sectional descriptive study was conducted between 2014 and 2015 on all hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Overall, a higher seroprevalence of HAV was generally reported among individuals residing in rural areas compared to urban areas, likely due to limited access to improved water sources and to sanitation facilities. 23 , 26 , 47 , 52 , 55 , 59 , 60 , 62 , 89 , 90 Four studies reported data on HAV seroprevalence by socioeconomic status; 21 , 23 , 75 , 81 collectively the data shows that individuals or families from low-income households (36.8 to 87.7%) had higher HAV seropositivity compared to individuals from middle- or high-income households (5.9 to 50.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a higher seroprevalence of HAV was generally reported among individuals residing in rural areas compared to urban areas, likely due to limited access to improved water sources and to sanitation facilities. 23 , 26 , 47 , 52 , 55 , 59 , 60 , 62 , 89 , 90 Four studies reported data on HAV seroprevalence by socioeconomic status; 21 , 23 , 75 , 81 collectively the data shows that individuals or families from low-income households (36.8 to 87.7%) had higher HAV seropositivity compared to individuals from middle- or high-income households (5.9 to 50.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatitis A virus is one of the most common etiologies of acute hepatitis worldwide 3 , infecting 212 million people per year, including 55 million symptomatic cases and 35,245 deaths globally 4 . As the number of asymptomatic infections is unknown, this number may be underestimated 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Different reports from Iran show a range of HAV prevalence from 8% to 99%. The most effective ways to combat hepatitis A are proving safe water supplies, food safety, improved public health and the hepatitis A vaccine [5][6][7][8]. During the past three decades, two major changes have been made.…”
Section: Introductionmentioning
confidence: 99%